2007
DOI: 10.1158/0008-5472.can-07-0982
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Can Suppress Tumorigenesis through Effects on the Putative Cancer Stem or Early Progenitor Cell and Committed Progeny in a Breast Cancer Xenograft Model

Abstract: The transforming growth factor-B (TGF-B) pathway has tumor-suppressor activity in many epithelial tissues. Because TGF-B is a potent inhibitor of epithelial cell proliferation, it has been widely assumed that this property underlies the tumor-suppressor effect. Here, we have used a xenograft model of breast cancer to show that endogenous TGF-B has the potential to suppress tumorigenesis through a novel mechanism, involving effects at two distinct levels in the hierarchy of cellular progeny that make up the epi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
79
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 48 publications
7
79
0
1
Order By: Relevance
“…This effect was associated with the activation of cytokine gene expression, suggesting that these cytokines may be involved in the P245-mediated inhibition of tumour growth (Pagliacci et al, 1993;Derynck et al, 2001;Shen et al, 2002;Underhill-Day and Heath, 2006). Interestingly, inhibition of breast cancer stem cells by TGF-b1 was reported recently (Tang et al, 2007) and TGF-b1 signalling is functional in CD44 þ breast cancer cells (Derynck et al, 2001). In the treated tumours, there was no evidence of decreased expression of the cell proliferation markers such as Ki67 or activation of apoptotic pathways.…”
Section: Discussionmentioning
confidence: 97%
“…This effect was associated with the activation of cytokine gene expression, suggesting that these cytokines may be involved in the P245-mediated inhibition of tumour growth (Pagliacci et al, 1993;Derynck et al, 2001;Shen et al, 2002;Underhill-Day and Heath, 2006). Interestingly, inhibition of breast cancer stem cells by TGF-b1 was reported recently (Tang et al, 2007) and TGF-b1 signalling is functional in CD44 þ breast cancer cells (Derynck et al, 2001). In the treated tumours, there was no evidence of decreased expression of the cell proliferation markers such as Ki67 or activation of apoptotic pathways.…”
Section: Discussionmentioning
confidence: 97%
“…In normal epithelial cells, TGF-b activates transcription of CDKN1A and CDKN2A, which encode the cyclin-dependent kinase (CDK) inhibitors, p21 CIP1 and p15 Ink4b respectively, causing cell-cycle arrest at the G 1 phase (Gomis et al 2006a). Conversely, TGF-b acting via a Smad -FoxO complex represses the transcription of MYC and ID family genes, which encode transcription factors that control cell proliferation, cell fate determination, and cellular differentiation Kondo et al 2004;Tang et al 2007;Anido et al 2010;James et al 2010). In carcinomas, many tumors lose the growth inhibitory response to TGF-b, but still respond to this ligand but in a protumorigenic manner, such as increased migration, invasion, and epithelial-mesenchymal transition (EMT).…”
Section: Inhibition Of Cell Proliferationmentioning
confidence: 99%
“…In support of this postulate, decreased expression of CSC markers was also detected in tumor cells of a single glioblastoma patient undergoing the first clinical trial of the small molecule TbRI inhibitor, galunisertib (Anido et al 2010). However, others made contrary findings in gastric carcinoma cells in culture and in a breast carcinoma xenograft model (Tang et al 2007;Ehata et al 2011). TbRISmad2 signaling has been implicated in maintaining epigenetic silencing that promotes and sustains EMT and the CSC phenotype (Papageorgis et al 2010).…”
Section: Tgf-b Action In Cancer Stem-cell Maintenancementioning
confidence: 99%
“…Specifically, a role for the TGFβ pathway in the maintenance of BTICs has been suggested, since EpCAM + /CD44 + / CD24 − /low cell subpopulations have an active TGFβ signalling pathway 22,23 . However, others have demonstrated that TGFβ suppresses tumorigenesis through inhibition of BTICs in a ER-negative (ER − ) breast cancer model 24 . In the experiments described here, we aimed to reconcile these observations by taking into account breast cancer heterogeneity.…”
mentioning
confidence: 99%